The jute marketing system in Bangladesh : an analysis of selected areas - Muazzam Husain, A. M. (Research report - Bureau of Agricultural Economic, Statistical, and Sociological, Research, Bangladesh Agricultural University., 1974)
Data collected during 1972 and 1973.